The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11164-011-0407-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the inhibitive effect of essential oil of Lavandula multifida L., on the corrosion behavior of C38 steel in 0.5 M H2SO4 medium

Abstract: The essential oil of the aerial parts of Lavandula multifida L., collected in Errachidia region (three samples) in southeast Morocco, was extracted by hydrodistillation and analyzed by GC and GC-MS. The oil was predominated by carvacrol (57.9-59.0%). L. multifida oil was tested as corrosion inhibitor of C38 steel in 0.5 M H 2 SO 4 using weight loss measurements, electrochemical polarization, and EIS methods. The results obtained by measurements of weight loss showed that inhibition efficiency increases with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…neoformans and dermatophyte ( Table 1). The high amounts of carvacrol in Portuguese L. multifida EOs are in accordance to those reported from Moroccan [25,48], and Algerian samples [49], nevertheless they must be considered different since cisβ-ocimene (2) also occurs in relatively high amounts, not observed for the Moroccan and Algerian samples. According to Khadir et al [50] and Messaoud et al [51], the EOs obtained from L. multifida collected in several places of Algeria or Tunisia, respectively, were predominantly constituted of carvacrol (3) and β-bisabolene (4).…”
Section: Lavandula Multifida Lsupporting
confidence: 84%
See 1 more Smart Citation
“…neoformans and dermatophyte ( Table 1). The high amounts of carvacrol in Portuguese L. multifida EOs are in accordance to those reported from Moroccan [25,48], and Algerian samples [49], nevertheless they must be considered different since cisβ-ocimene (2) also occurs in relatively high amounts, not observed for the Moroccan and Algerian samples. According to Khadir et al [50] and Messaoud et al [51], the EOs obtained from L. multifida collected in several places of Algeria or Tunisia, respectively, were predominantly constituted of carvacrol (3) and β-bisabolene (4).…”
Section: Lavandula Multifida Lsupporting
confidence: 84%
“…Lavandula multifida (fern leaf lavender, Egyptian lavender) is a species of the section Pterostoechas occurring commonly along the Mediterranean coast (Egypt, Tunisia, Morocco, Algeria, Spain, Portugal). In Italy, the plant has been found in the hot and arid climatic conditions of Calabria and Sicily [22,23], whereas in Tunisia the plant can be found in upper semi-arid bioclimates, particularly in open calcareous garrigues [24]; and in Morocco it also grows on calcareous soils and on the borders of rivers of temporary drainage, between 800 and 2000 m altitude [25]. In Portugal, L. multifida grows in the southern region (Sesimbra, Arrábida and Mértola) [23].…”
Section: Lavandula Multifida Lmentioning
confidence: 99%
“…More recently, Lavender oil has been found to be not harmful to the environment as corrosion inhibitor, Halambek et al [17] have carried out a study on the influence of Lavandula angustifolia L. on corrosion of Al-3 Mg alloy in 3% NaCl solution, the results showed an efficiency of 99% for a concentration of 20 ppm at 25 °C. The study by Znini et al [18] on the uses of Lavandula multifida L. oil as a corrosion inhibitor in 0.5 M H 2 SO 4 medium, showed that the oil exhibited a high inhibition efficiency of 72.2% at 2 g/L of oil at 25 °C, the usage of L. stoechas oil, abstracted from leaves as corrosion inhibitor of stainless steel in H 3 PO 4 solution was elaborated by Boudalia et al [19]. The inhibitory efficiency was 87.3% at 1.2 g/L at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, a great deal of research has been carried out to study inhibitive effect using plant extract on the corrosion of steel in acidic media. [14][15][16][17][18][19] . In this study, our focus is chiefly put on the essential oil of Santolina pectinata (Lag.)…”
Section: Introductionmentioning
confidence: 99%